2021
DOI: 10.1055/s-0041-1726502
|View full text |Cite
|
Sign up to set email alerts
|

New Standards for Clinical Decision Support: A Survey of The State of Implementation

Abstract: Summary Objectives: To review the current state of research on designing and implementing clinical decision support (CDS) using four current interoperability standards: Fast Healthcare Interoperability Resources (FHIR); Substitutable Medical Applications and Reusable Technologies (SMART); Clinical Quality Language (CQL); and CDS Hooks. Methods: We conducted a review of original studies describing development of specific CDS tools or infrastructures using one of the four targeted standards, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
(47 reference statements)
0
14
0
Order By: Relevance
“… 30 The few studies on the efficacy of publicly available, standards-based CDS generally focus on new products and the design or pilot stages of CDS development, rather than outcomes. 13 Yet, we found that demonstrating a return on investment (ROI) is critical to promoting CDS uptake.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“… 30 The few studies on the efficacy of publicly available, standards-based CDS generally focus on new products and the design or pilot stages of CDS development, rather than outcomes. 13 Yet, we found that demonstrating a return on investment (ROI) is critical to promoting CDS uptake.…”
Section: Resultsmentioning
confidence: 97%
“…10,11 See ►Table 1 for description. 12,13 Only two publicly available repositories make EHR-agnostic CDS artifacts and resources freely available. One, OpenCDS, is a collaborative community that leverages open-source tooling and services to support modular development of standards-based CDS.…”
Section: Background and Significancementioning
confidence: 99%
“…We developed our search strategy by first using existing published strategies. To identify publications about CDS, we adopted the strategy developed by Bright et al [17], then expanded to include additional search terms identified through more recent reviews [18,19], such as "best practice advisory." We then limited the publications using the MEDLINE®/PubMed® Health Disparities and Minority Health Search Strategy [20] and search terms for digital divide.…”
Section: Search Strategymentioning
confidence: 99%
“…Now, doctors are using CDSS more and more in many different areas, such as infection management [2], care for the elderly [3], [4], diabetes mellitus [5], chemotherapy [6], fractures [7], and cardiovascular [8]. However, the rarity of reported evaluations, as well as the high number of studies in the design or pilot phase, suggest that the use of this CDSS to support decision making is considered new and requires further study [9]. When CDSS is used correctly, it makes it possible to combine human intelligence and artificial intelligence, which are both good at doing empirical tasks [10].…”
Section: Introductionmentioning
confidence: 99%